"Mãe Mariana pede, a gente faz" um estudo antropológico da relação do Pai de Santo com o altar da Cabloca Mariana - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2014)
How are produced, felt and understood the relation between the pai de santo from Terreiro de Mina Santa Bárbara with the Altar of his entidade the Cabocla Mariana? This is the question that directs the ethnographic material of this research. About the afro-Brazilian religious manifestations I discuss some results and analysis about the uses and meanings of the Objetos and Elementos Sagrados in a terreiro de Umbanda located in Santarém (PA). Doing use of the ethnographic one and observation participant, the study comes permitting understand the connection of the Pai de Santo with the forças of the Cabocla Mariana. In the perspective of the priest the Objetos located in spaces considered Sagrados emanate forças that influence behaviors, feelings and sensations, performing an important elo in the social life of the religious group.
Keywords: Altar; Cultura material; Práticas simbólicas; Religião Afro-brasileira; CNPQ:: CIÊNCIAS HUMANAS